First Composite Woman-to-Woman Facial Transplantation in Turkey: Challenges and Lessons to Be Learned. Issue 1 (January 2023) - Ozmen, Selahattin; Findikcioglu, Kemal; Sibar, Serhat; Tuncer, Serhan; Ayhan, Suhan; Guz, Galip; Unal, Yusuf; Aslan, Selcuk
Abstract: After the first face transplantation from woman to woman we performed in our clinic, it was aimed to eliminate the lack of knowledge about the subject in the literature by transferring our experiences and long-term results to the problems we had with the patient. A 20-year-old patient underwent partial osteomyocutaneous facial transplant (22nd facial transplant), which included 2 functional units of the face. The patient had no major problems in the early period and had a good aesthetic appearance. In the postoperative period, the patient ended her social isolation and adopted the transplanted face. In the late period, secondary surgical interventions, management of the problems caused by immunosuppression, and the patient's living in a remote location to our clinic were the difficulties encountered. Six revision surgeries were performed after the transplantation. Due to immunosuppression, opportunistic infections and metabolic problems required intermittent hospitalization. The patient died at the end of 56 months because of complications secondary to immunosuppression. A successful transplant involves the management of long-term problems rather than a successful tissue transfer in the early period. In today's conditions, long-term success can be achieved with a good patient compliance, as well as each team member should take an active role in the team at the transplantation centers. More case series are needed to adapt the standard treatment and follow-up protocols for solid organ transplantations for composite tissue allotransplantations. This will be possible by sharing the results and experiences transparently in the centers where face transplantation is performed worldwide.